Amplified loci on chromosomes 8 and 17 predict early relapse in ER-positive breast cancers. - Erhan Bilal; Kristen Vassallo; Deborah Toppmeyer; Nicola Barnard; Inga H Rye; Vanessa Almendro; Hege Russnes; Anne-Lise Børresen-Dale; Arnold J Levine; Gyan Bhanot; Shridar Ganesan (PLoS ONE, 2012)
Adjuvant hormonal therapy is administered to all early stage ER+ breast cancers, and has led to significantly improved survival. Unfortunately, a subset of ER+ breast cancers suffer early relapse despite hormonal therapy. To identify molecular markers associated with early relapse in ER+ breast cancer, an outlier analysis method was applied to a published gene expression dataset of 268 ER+ early-stage breast cancers treated with tamoxifen alone. Increased expression of sets of genes that clustered in chromosomal locations consistent with the presence of amplicons at 8q24.3, 8p11.2, 17q12 (HER2 locus) and 17q21.33-q25.1 were each found to be independent markers for early disease recurrence. Distant metastasis free survival (DMFS) after 10 years for cases with any amplicon (DMFS = 56.1%, 95% CI = 48.3-63.9%) was significantly lower (P = 0.0016) than cases without any of the amplicons (DMFS = 87%, 95% CI = 76.3% -97.7%). The association between presence of chromosomal amplifications in these regions and poor outcome in ER+ breast cancers was independent of histologic grade and was confirmed in independent clinical datasets. A separate validation using a FISH-based assay to detect the amplicons at 8q24.3, 8p11.2, and 17q21.33-q25.1 in a set of 36 early stage ER+/HER2- breast cancers treated with tamoxifen suggests that the presence of these amplicons are indeed predictive of early recurrence. We conclude that these amplicons may serve as prognostic markers of early relapse in ER+ breast cancer, and may identify novel therapeutic targets for poor prognosis ER+ breast cancers.